(untitled) (Práxis Educativa, 2024)
For decades, oral tradition has transmitted from generation to generation, from grandparents to parents and their children, the culture of society through stories, legends, songs, riddles, proverbs, among others. Research objective that sought to determine if there is a direct relationship between oral tradition and didactics in the area of communication. Descriptive correlational research, with a non-probabilistic sampling of 36 elementary school students from the community of Sharanahua in the province of Purús Ucayali in Peru, who were administered two questionnaires validated through expert judgment whose Cronbach’s alpha reliability analysis was 0.70 for the oral tradition variable and 0.86 for didactics in the area of communication. The results show that there is no significant correlation between oral tradition and communication didactics in primary education in the province of Purús-Ucayali. In conclusion, there is no relationship between the oral tradition variables and the dimensions of the communication didactics variable: comprehension of oral texts, oral expression, comprehension of written texts and production of written texts. Keywords: Didactics. Education. Spoken language. Storytelling. Tradition.